PENDIDIKAN PRA NIKAH SEBAGAI INSTRUMEN MENGURANGI ANGKA PERCERAIAN - Saragih, Alkausar (LP2M Universitas Muslim Nusantara Al Washliyah, 2025)
The high divorce rate is a serious problem that impacts family resilience and social stability. One strategic preventive measure to reduce the divorce rate is through premarital education. This article aims to analyze the role of premarital education as an instrument in reducing divorce and examine its contribution to building the mental, emotional, spiritual, and social readiness of prospective married couples. This research uses a qualitative approach with a literature review method, sourced from books, journal articles, government regulations, and documents related to family and marriage education. The results of the study indicate that premarital education plays a crucial role in providing a comprehensive understanding of the rights and obligations of husband and wife, effective communication, conflict management, and religious values ​​in building a harmonious household. Premarital education also contributes to minimizing factors that cause divorce, such as psychological unpreparedness, weak understanding of family roles, and low religious literacy. Thus, premarital education can be seen as an effective preventive instrument in strengthening family resilience and reducing the divorce rate.